The Implementation of Technology in School Learning Over the Last 50 Years: A Bibliometric Analysis of the Scopus Database - Yoel Istiawanto; Syukrul Hamdi; Zafrullah Zafrullah; Yanti Kumala Sembiring (Postgraduate, University of Mataram, 2024)
This research aims to analyze research trends in the field of technology use in the school environment. Using predetermined keywords, researchers selected documents using the PRISMA method and obtained 599 final documents which were analyzed using the R Program Biblioshiny, Publish or Perish 8, and VOSviewer to map trends in research results with bibliometric analysis. From this analysis it can be concluded that research on the use of technology in the school environment began in 1974 until 2024 with peak publications in 2023 and peak citations in 2018. The United States is the most productive country in the field of most productive countries. Nanyang Technological University is the most productive affiliate, recording the highest number of publications. Journal Q1